An unusual local invasion of synovial sarcoma. Issue 4 (16th April 2019) - Minami, Yusuke; Matsumoto, Seiichi; Ae, Keisuke; Sugiura, Yoshiya
Abstract: Synovial sarcoma is a malignant tumor, it accounts for approximately 5–10% of the soft tissue sarcoma, and mainly develops in the para-articular regions in adolescents and young adults. We reported a case of synovial sarcoma extending into the vastus intermedius muscle beyond the intermuscular septum which is considered to be the greatest barrier to ensuring a safety margin in musculoskeletal surgery. Preoperative sequential MRI showed the intermuscular-septum line and direct tumoral invasion beyond the intermuscular septum. A histopathological examination showed the direct invasion to the intermuscular septum. Synovial sarcoma seldom shows such direct invasive pattern to barriers, much less the robust barrier like an intermuscular septum. To our knowledge, no previous study has reported such unique extension of a synovial sarcoma beyond the intermuscular septum. Surgeons should be aware of the potential vulnerability of the intermuscular septum.